Functional results and complications of Mersilene mesh use for frontalis suspension ptosis surgery. Issue 3 (20th February 2004) - Mehta, P; Patel, P; Olver, J M
Abstract : Aims: To assess the functional results and complications of Mersilene (polyester) mesh frontalis sling suspension to correct poor levator function ptosis. Methods: Retrospective case series. 32 eyelids of 20 patients (12 children and eight adults). Results: Follow up 1–69 months (mean 32). Children : eight patients had bilateral and four unilateral surgery (20 eyelids). Good long term functional results were achieved in 73% (8/11 children) and 77% (14/18) eyelids. Two children had early postoperative wound infection requiring removal of mesh in one; the other was lost to follow up following medical treatment. Adults : four patients had bilateral and four unilateral surgery (12 eyelids). Good long term functional results were achieved in 75% (6/8 patients, 9/12 eyelids). One postoperative wound infection and one mesh exposure were treated definitively by surgical excision of mesh. Conclusion: Mersilene mesh provides good functional results but up to 20% of patients have early soft tissue complications. Other materials such as monofilament suture or autogenous fascia lata should be considered.